التدابير والإجراءات القانونية الدولية لمكافحة الصيد البحري الغير القانوني وغير المنظم وغير المبلغ عنه - صبحي, رفيق (University of Eloued جامعة الوادي, 2021)
أصبحت ظاهرة الصيد الغير القانوني وغير المنظم وغير المبلغ عنه، تشكل أكبر تهديد للتنمية المستدامة لمصائد الأسماك البحرية في العالم، مما جعل المجتمع الدولي وعلى رأسهم منظمة الأمم المتحدة ووكالاتها المتخصصة، خاصة منظمة الأغذية والزراعة العالمية، تناشد في عدة مؤتمرات دولية معنية بالبيئة والتنمية المستدامة، إلى ضرورة اتخاذ إجراءات وتدابير جديدة لمنع هذه الظاهرة، وتلبية لهذه النداءات بذل المجتمع الدولي، جهود كبيرة كللت بوضع صكوك قانونية دولية ملزمة وغير ملزمة، هدفها ضمان استدامة استغلال الموارد السمكية، والالتزام بحفظها وإدارتها لمنفعة الأجيال الحاضرة والمقبلة، والقضاء على الصيد المفرط. :Abstract The phenomenon of illegal, unregulated and unreported fishing has become the biggest threat to the sustainable development of marine fisheries in the world, which made the international community, led by the United Nations and its specialized agencies, especially the World Food and Agriculture Organization to appeal in several international conferences on the environment and sustainable development, The need to take new measures and procedues to prevent this phenomenon to meet to these calls, the international community made great efforts that culminated in developing binding and non-binding international legal instruments aimed at ensuring the sustainability of the exploitation of fish resources, the commitment to preserve and manage them for the benefit of present and future generations, and the elimination of overfishing.
International legal measures and procedures to against sea fishing Illegal unregulated and unreported
مقال
Keywords: الصيد البحري ; السمكية ; الاجراءات ; تدابير ; منظمات ; اقليمية; fishing; Fish resources; Measures; Procedures Organizations; Regional.